1989
DOI: 10.1007/bf01911882
|View full text |Cite
|
Sign up to set email alerts
|

On the methods of solving the inverse problem of solid-phase reaction kinetics

Abstract: The second part of this review deals with the methods of inverse kinetic problem (IKP) solving based on generalized descriptions of the process. The application of these methods is considered an alternative (for discrimination) approach to IKP solving. It is shown that the base of this approach is the methodology of complementarity. Different types of generalized descriptions, their merits and their shortcomings are discussed.As noted in the first part of this review, the unambiguous description methods reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 106 publications
0
12
0
Order By: Relevance
“…Vyazovkin and Lesnikovich [22] have indicated that the kinetic parameters for decomposition processes calculated from isothermal data are generally model independent, but those calculated from non-isothermal data are very dependent upon the chosen kinetic model. Thus, under most circumstances, the preferred method for obtaining the Arrhenius parameters for decomposition processes is from isothermal data.…”
Section: Resultsmentioning
confidence: 99%
“…Vyazovkin and Lesnikovich [22] have indicated that the kinetic parameters for decomposition processes calculated from isothermal data are generally model independent, but those calculated from non-isothermal data are very dependent upon the chosen kinetic model. Thus, under most circumstances, the preferred method for obtaining the Arrhenius parameters for decomposition processes is from isothermal data.…”
Section: Resultsmentioning
confidence: 99%
“…The SB approach offers two distinct theoretical advantages [205]: (1) no implicit assumptions are made concerning the mechanism governing the solid state reaction and (2) no approximations or heavy-handed mathematical intricacies are involved as the values of c, d, and e can be calculated directly using a matrix system of linear equations. Vyazovkin and Lesnikovich [206] acknowledged the importance of the generalized description afforded by the SB equation, remarking that ". .…”
Section: Other Kinetic Modelsmentioning
confidence: 99%
“…Subsequently, k(T) can be evaluated by the form of f(α) chosen. This is a limitation because the calculated kinetic parameters are very dependent upon the chosen kinetic model [67]. For zero-order processes, the degradation rate can be represented in integrate form as:…”
Section: Kinetic Parameters and Modellingmentioning
confidence: 99%